“Reduced public coverage did not decrease dental visits”: fact or fiction? - Sarroukh, Ziade; Jeurissen, Patrick; Listl, Stefan (Journal of dental research, 2025)
Challenges of access have sparked political debates about dental coverage in the Netherlands. So far, policy makers have been opposing an expansion of public coverage for the adult population, arguing that previous reductions of public coverage would not have led to reduced dental attendance within the Dutch population. To this end, this study aims to evaluate the effects of public coverage reductions since 1995 on dental care utilization. We used a population-wide data set from Statistics Netherlands containing dental care utilization rates across insurance- and age-based subpopulations between 1981 and 2019. Drawing from an interrupted time series design with segmented regressions, we evaluated how scaling down public coverage for curative dentistry in 1995 and preventive dentistry in 2004 affected dental attendance. Population groups that were not subject to the reforms served as control groups (i.e., nonadult population and privately insured persons). Following the 1995 reform and in comparison with privately insured persons (control group), the dental attendance of publicly insured persons (intervention group) decreased by an immediate 3.5 percentage points (95% CI, −5.8 to −1.1) and by a subsequent 0.6 percentage points (95% CI, −0.9 to −0.3) per year. When compared with that of the nonadult population (control group), dental attendance by 20- to 45-y-olds (intervention group) immediately dropped by 4.6 percentage points (95% CI, −7.0 to −2.1) and subsequently by 1.2 percentage points (95% CI, −1.5 to −0.8) per year. Contrary to Dutch policy makers’ arguments, our findings suggest that reduced public coverage led to fewer people visiting the dentist in the Netherlands. These findings highlight the central role of policy evaluation for evidence-informed oral health policy making.